GEOLOGIC ASPECTS CONTROLLING MACERAL AND MINERAL MATTER CONTENT OF SATUI COALS- SOUTH KALIMANTAN - BINARKO SANTOSO (Puslitbang tekMIRA, 2011)
Coal deposits were formed in Tertiary sequexnces in Satui area of Asem-Asem Basin, South Kalimantan. The coals were deposited in paralic to neritic environments. Lithotype of Satui coals is dominated by bright- banded and banded. Petrographically, vitrinite and liptinite are the dominant macerals in the Eocene coals. Inertinite is a minor component. Mineral content is relatively high in most of the coals. There is a significant relationship between lithotype and petrographic observations; the brighter coal is in association with the vitrinite-rich coal. The differences in the coal type are due to the interaction of geologic factors. There is a good correlation among lithotype, petrographic composition and geologic aspects that clearly influence the characteristics of the coals. The ranks of the Eocene coals ranging from brown coal to high volatile bitumi- nous indicate a normal regional coalification.